Pengukuran Faktor-Faktor yang Memengaruhi Wanita Membeli Pangan Organik (Healthy- Diet) Berbasis Teori Perilaku Terencana - Imam Santoso; Arif Julianto sri Nugroho; Heru Murjito; Dwi Wanito Ambarsari; Tasari Tasari; Endang Eko Djati S; Sukasih Ratna W. (Journal of Business and Economics Research (JBE), 2023)
This study aims to conduct a multivariate test of the dependent variable on women’s behaviour of buying healthy-diet which are influenced by three independent variables, namely attitude, knowledge, and subjective norm. The research object as the sample is women costumers in Klaten who buy Srinuk organic rice and organic food around 100 respondents with purposive sampling. The data analysis in this study is in the form of respondent description tests, validity and reliability tests of items, and variable regression tests which are useful for providing an image of perception in the society’s mind regarding the proof of buying behaviour model for organic food. Quantitative test multivariate used AMOS Software. The test results found that the attitude CR 5.457 prob 0.03 and knowledge variables 5.457 prob 0.03 proof which influenced buying behaviour, while one subjective norm variable CR 3.150 and prob 0.646 had no significant effect. From the research findings of the model evidence, a strategy is needed for stakeholders to develop marketing strategies towards the competitive advantage of organic food towards the increase of public consumption with more favourable products and market developments. At a later stage, it is possible to conduct experimental research.